Pendampingan Strategi Pemasaran Pada Young Entrepreneurs Start-Up Di Gresik Pada Era New Normal - Suaibatul Aslamiyah; Prayudi Harianto (Jurnal Pengabdian Manajemen, 2023)
The New Normal era provides a great opportunity for companies to increase their turnover, but under different conditions the company faces marketing constraints (Ahmad, A.and, Nurhidaya, 2020). Facing the New Normal era, new economic drivers are needed, namely MSMEs and entrepreneurs, or what is now widely known as start-up. Entrepreneurship needs to be encouraged to increase national economic growth. This is because this sector is able to absorb as much as 97 percent of the total national workforce. In addition, the New Normal Era is a new challenge for MSMEs, including Young Entrepreneurs Start-up. They have become MSMEs which are now starting to be taken into account and dominated by Millennials, including in Gresik. This service aims to provide marketing strategy assistance using e-marketing by utilizing the currently trending TikTok Shop. The method used is Participatory Rural Appraisal (PRA), namely approaches and techniques for involving the community in thought processes that take place during planning, implementation and monitoring and evaluation of community development programs. At the time of implementation, the activity was followed by 12 Young Entrepreneurs Start-up in Gresik. E-marketing assistance activities use the "TikTok Shop" application which is currently a trending social media among millennials through Google Playstore via Playstore with the search key "TikTok". As a result of the implementation of this service, there was an increase in the ability of Young Entrepreneurs Start-up to utilize social media TikTok for e-marketing as well as in terms of business development and product promotion at low cost and affordable and up to date.